A Submillimeter Continuous Variable Stiffness Catheter for Compliance Control (Adv. Sci. 18/2021). Issue 18 (22nd September 2021) - Lussi, Jonas; Mattmann, Michael; Sevim, Semih; Grigis, Fabian; De Marco, Carmela; Chautems, Christophe; Pané, Salvador; Puigmartí‐Luis, Josep; Boehler, Quentin; Nelson, Bradley J.
Abstract : Variable Stiffness Catheter In article number 2101290 by Quentin Boehler, Bradley J. Nelson, and co‐workers, a magnetically controlled catheter that is able to continuously change its stiffness is presented. Soft, magnetic tools that are enhanced with the capability to apply and control forces during surgical intervention can significantly improve outcome of the procedure. The capabilities are demonstrated by performing a fully robotic surgery for a challenging ophthalmic intervention. Image designed by Adrián Bago González.